Arthroscopic Trapeziectomy and Suture Button Suspensionplasty: A Review of the Literature and Description of the “Three-Step Arthroscopic Trapeziectomy Technique” - Corella, Fernando; Ocampos, Montserrat; Laredo, Rafael; Tabuenca, José; Carnicer, Maribel; Larrainzar-Garijo, Ricardo (Journal of Wrist Surgery, 2020)
In the last two decades, surgeons have rapidly developed arthroscopic techniques to treat basal joint osteoarthritis. Such techniques spare the joint capsule and ligaments, allow more accurate staging of cartilage degeneration to determine the most appropriate treatment, and decrease the risk of injury to the radial artery and superficial branch of the radial nerve. Arthroscopic resection arthroplasty of the trapezium can be performed as either partial or complete trapeziectomy. Many papers have described partial trapeziectomy but few have discussed complete trapeziectomy.Suture button implants avoid the drawbacks of temporary fixation using Kirschner wire, as well as the drawbacks of ligament reconstruction, which necessitates the sacrifice of a tendon and involves both wide exposure and scar tissue.This paper aimed to review the published data on the arthroscopic treatment of basal thumb osteoarthritis, with a special focus on stabilization using suture button suspensionplasty, and to present a technique that structures this procedure into three steps, allowing it to be performed in an easier, more organized, and faster way.
Keywords: arthroscopic trapeziectomy; thumb; suture button suspensionplasty; thumb osteoarthritis